Alternative methods for toxicity assessments in fish: Comparison of the fish embryo toxicity and the larval growth and survival tests in zebrafish and fathead minnows. (19th September 2014) - Jeffries, Marlo K. Sellin; Stultz, Amy E.; Smith, Austin W.; Rawlings, Jane M.; Belanger, Scott E.; Oris, James T.
Abstract An increased demand for chemical toxicity evaluations has resulted in the need for alternative testing strategies that address animal welfare concerns. The fish embryo toxicity (FET) test developed for zebrafish (Danio rerio) is one such alternative, and the application of the FET test to other species such as the fathead minnow (Pimephales promelas) has been proposed. In the present study, the performances of the FET test and the larval growth and survival (LGS; a standard toxicity testing method) test in zebrafish and fathead minnows were evaluated. This required that testing methods for the fathead minnow FET and zebrafish LGS tests be harmonized with existing test methods and that the performance of these testing strategies be evaluated by comparing the median lethal concentrations of 2 reference toxicants, 3, 4‐dicholoraniline and ammonia, obtained via each of the test types. The results showed that procedures for the zebrafish FET test can be adapted and applied to the fathead minnow. Differences in test sensitivity were observed for 3, 4‐dicholoraniline but not ammonia; therefore, conclusions regarding which test types offer the least or most sensitivity could not be made. Overall, these results show that the fathead minnow FET test has potential as an alternative toxicity testing strategy and that further analysis with other toxicants is warranted in an effort to better characterize the sensitivity and feasibility of this testing strategy. Environ Toxicol Chem 2014;33:2584–2594. © 2014 SETAC